Wellness forecasting by external and internal workloads in elite soccer players: A machine learning approach - Rossi, A.; Perri, E.; Pappalardo, L.; Cintia, P.; Alberti, G.; Norman, D.; Iaia, F. M. (Frontiers in Physiology, 2022)
Training for success has increasingly become a balance between maintaining high performance standards and avoiding the negative consequences of accumulated fatigue. The aim of this study is to develop a big data analytics framework to predict players` wellness according to the external and internal workloads performed in previous days. Such a framework is useful for coaches and staff to simulate the players` response to scheduled training in order to adapt the training stimulus to the players` fatigue response. 17 players competing in the Italian championship (Serie A) were recruited for this study. Players` Global Position System (GPS) data was recorded during each training and match. Moreover, every morning each player has filled in a questionnaire about their perceived wellness (WI) that consists of a 7-point Likert scale for 4 items (fatigue, sleep, stress, and muscle soreness). Finally, the rate of perceived exertion (RPE) was used to assess the effort performed by the players after each training or match. The main findings of this study are that it is possible to accurately estimate players` WI considering their workload history as input. The machine learning framework proposed in this study is useful for sports scientists, athletic trainers, and coaches to maximise the periodization of the training based on the physiological requests of a specific period of the season.